The Role Of Islamic Education Teachers In Increasing Social Awareness And Environmental Awareness In The Young Generation - Sahri, Sahri; Aziz, Su'udin (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
Purpose this article discusses the important role of Islamic religious education teachers in increasing social awareness and environmental awareness in the younger generation. Islamic religious education has a strategic role in shaping students' character and morals, including awareness of social and environmental issues. Teachers of Islamic religious education have the responsibility to integrate religious values with social and environmental issues in the learning process. This type of research is literature research. Data collection by observation and documentation. The result of this study is the existence of Islamic values that include ethics and social responsibility towards the environment. Teachers are also expected to be exemplary examples of practicing these values in everyday life. Through creative and interactive teaching strategies, teachers can help students understand the importance of caring for fellow humans and the environment and their role as agents of change.   Keywords: Teacher, Islamic Education, Social, Environmental Concern